Effect of the addition of diatoms (Navicula spp.) and rotifers (Brachionus plicatilis) on water quality and growth of the Litopenaeus vannamei postlarvae reared in a biofloc system. (23rd July 2015) - Brito, Luis Otavio; dos Santos, Itala Gabriela Sobral; de Abreu, Jéssika Lima; de Araújo, Marcele Trajano; Severi, William; Gàlvez, Alfredo Olivera
Abstract: The aim of this study was to evaluate the effect of the addition of Navicula spp. and Brachionus plicatilis on water quality and growth of postlarvae shrimp Litopenaeus vannamei reared in a biofloc system. Four treatments were considered: a control (biofloc system – BFT); BFT with the addition of Navicula spp. (BFT‐N); BFT with the addition of Brachionus plicatilis (BFT‐B) and BFT with the addition of Navicula spp. and Brachionus plicatilis (BFT‐NB), each in triplicate. Shrimp (16.2 ± 0.03 mg) were stocked at a density of 2500 shrimp m −3 and plankton were added on days 1, 5, 10, 15, 20, 25 and 30 at a density of 5 × 10 4 cells mL −1 ( Navicula spp.) and 30 organisms L −1 ( Brachionus plicatilis ). The shrimp were fed a formulated feed in four daily rations composed of 40% crude protein and 8% lipids. Significant differences between treatments were observed for final weight, yield, feed conversion ratio, specific growth rate, protein efficiency ratio and protein content of the shrimp. The combined plankton addition of Navicula spp. and B. plicatilis had better performance parameters, indicating their benefit as natural food sources for postlarvae L. vannamei in biofloc systems.